Pengaruh Intensitas Bermain Game Online Terhadap Hasil Belajar PAI Peserta Didik Generasi Milenial di SMP Nurul Amal Palembang - Ma'ruf, Imam; Tauhid, Imam; Hasanah, Laila Rahmi; Purnomo, Mulyadi Eko; Oviyanti, Fitri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Online games which are currently popular have indirectly made students focus more on online games or games on their smartphones compared to studying, and this is a concern because it can affect student learning outcomes. This research aims to find out and analyze how much intensity students play online games and to find out the effect of the intensity of playing online games on student learning outcomes at SMP Nurul Amal Palembang. This research is a quantitative research type with a sample size of 57 students. The results of the research that has been conducted obtained data that the intensity of playing online games as many as 1 person or 2% got the high category, 53 people or 90% got the medium category and 4 people or 8% got the low category. then the final semester grades in the Islamic Religious Education subject that got the high category were 2 people or 4%, those who got the medium category were 48 people or 84% and those who got the low category were 7 people or 12%. So it can be concluded that the intensity of playing online games has a significant influence on the learning outcomes of millennial generation students of SMP Nurul Amal Palembang. 147